Evaluasi Manfaat Program Jaminan Kesehatan Daerah bagi Masyarakat Kota Yogyakarta - Rohadanti Rohadanti; Sigit Riyarto; Retna Siwi Padmawati (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: The Program of Community Health Insurance Scheme (Jamkesda) in Yogyakarta Municipality is organized by the Technical Unit Regional Health Insurance Provider (UPT PJKD) with funds from the municipal budget. The rules about membership, benefits and amount of Jamkesda are appointed in the Mayor Regulation. There has been no comprehensive research about benefits and the perceived difficulty when using Jamkesda. Therefore, this research aims to determine this issue. Methods: This was an observational study using quantitative and qualitative methods. The quantitative respondents (n= 154) were selected accidentally when the patients were being treated at two hospitals in Yogyakarta and were based on the recapitulation of the claims in the previous month. The qualitative respondents (n = 10) were selected by purposive sampling for patients with chronic illnesses and with very high claims. Data collection was taken by questionnaire and guide- line for in-depth interviews to Jamkesda participants who had been treated in the two hospitals. Results: The respondents perceived that Jamkesda was beneficial despite objecting to 51.30% of the cost sharing. Therefore, in in-depth interviews five respondents expressed that they had to borrow money to pay for it. A total of 61.04% respondents used a letter of recommendation from Department of Social, Labor and Transmigration (those with no health insurance). Difficulty in handling the identity of membership was only experienced by 16.23%, while 78.57% had no prob- lem in it. Those who found difficulty were looking for a solution to the government administrator as RT/RW, parliaments, NGOs and neighbors. Around 78.57% of respondents did not under- stand about the Jamkesda service limit; they only knew infor- mation relating to their current interests. A total of 89.61% respondents knew that Jamkesda was an aid. All respon- dents in in-depth interview and around 73.38% respondents paid the cost sharing more than 10% of total claims. From the total household expenditure, almost all (99.35 %) were cata- strophic as the health spent more than 40% of their household expenditure whereas 73.38% earned below the minimum wage income. Conclusion: High cost sharing can result in large catastrophic expenses. Therefore, there is a need for reassessing the Jamkesda benefit package in order that the financial protec- tion of household can be achieved.Latar Belakang: Program Jaminan Kesehatan Daerah (Jam- kesda) Kota Yogyakarta diselenggarakan oleh Unit Pelaksana Teknis Penyelenggara Jaminan Kesehatan Daerah (UPT PJKD) dengan sumber dana berasal dari APBD Kota Yogyakarta. Aturan tentang kepesertaan, benefit dan besarannya terdapat dalam Peraturan Walikota. Belum ada penelitian yang kompre- hensif tentang manfaat dan kesulitan yang dirasakan masya- rakat dalam menggunakan Jamkesda Kota Yogyakarta maka penelitian ini bertujuan untuk mengetahui hal tersebut. Metode: Penelitian ini adalah penelitian observasional dengan metode kuantitatif dan kualitatif. Responden kuantitatif (n=154) dipilih secara accidental ketika pasien sedang berobat di dua rumah sakit di Yogyakarta dan didasarkan pada rekapitulasi klaim pada bulan sebelumnya. Responden kualitatif (n=10) dipilih dengan purposive sampling yaitu pasien dengan penyakit kro- nis dan yang mempunyai klaim sangat tinggi. Pengumpulan data menggunakan kuesioner dan pedoman wawancara men- dalam kepada peserta Jamkesda yang sedang atau telah dira- wat di dua RS tersebut. Hasil: Responden merasakan manfaat Jamkesda walaupun 51,30% merasa keberatan dengan besar cost sharing, se- hingga sebagian responden pada wawancara mendalam me- nyatakan mengutang untuk membayarnya. Sebanyak 61,04% responden menggunakan surat rekomendasi Dinas Sosial Tena- ga Kerja dan Transmigrasi untuk berobat karena tidak memiliki jaminan kesehatan. Kesulitan dalam pengurusan identitas kepe- sertaan hanya dialami oleh 16,23%, sedangkan 78,57% merasa mudah dalam pemanfaatannya. Masyarakat yang merasa kesu- litan pada wawancara mendalam, mencari solusi kepada pe- ngurus RT/RW, anggota DPRD, LSM dan tetangga. Sekitar 78,57% responden tidak memahami batasan pelayanan Jam- kesda dan hanya mengetahui informasi yang berhubungan dengan kepentingan mereka saat itu. Sebanyak 89,61% res- ponden mengetahui bahwa Jamkesda hanya bersifat bantuan. Semua responden pada wawancara mendalam serta 73,38% responden membayar cost sharing lebih dari 10% total klaim dari pengeluaran rumah tangga, hampir semua (99,35% res- ponden) mengalami pengeluaran katastrofik yakni pengeluaran biaya kesehatan lebih dari 40% pengeluaran rumah tangga setelah dikurangi pengeluaran kebutuhan pokok padahal 73,38% masyarakat berpenghasilan di bawah UMR. Kesimpulan: Cost sharing yang besar dapat berakibat pe- ngeluaran katastrofik sehingga perlu dikaji kembali benefit pack- age Jamkesda agar perlindungan terhadap keuangan rumah tangga dapat dicapai.